A study on laser-fibre coupling efficiency and ablation rate in femtosecond laser deep microdrilling. (1st January 2012) - Shen, Xinwei; Bian, Qiumei; Chang, Zenghu; Lei, Shuting; Wu, Benxin
Laser microdrilling is a common micromachining operation in many industrial applications. This paper presents a new laser microdrilling technique in which a hollow-core fibre is employed to transmit femtosecond laser pulses to the target position. The coupling efficiency between the laser and the fibre is investigated and found to be strongly related to pulse energy and pulse duration. A parametric study on the ablation rate indicates that in microdrilling of a stainless steel (type 303), the operating parameters including pulse energy, pulse duration, sample thickness, focal length and sample-fibre distance can affect the ablation rate. The experimental results show that the new technique developed in this study is feasible to conduct microdrilling of holes with high aspect ratio.